Mechanistic insights into triclosan-induced hepatotoxicity: A network toxicology and molecular docking approach - Fuzhi Liu; Yanyan Zhao; Dandan Zhu; Jingwen Wang; Zhaocheng Zhuang; Yangjia Chen; Yuan Su; Zhuote Tu (PLoS ONE, 2026)
Background Triclosan (TCS) is an artificially synthesized broad-spectrum antimicrobial agent, which is widely used in personal care products. It is a new endocrine disruptor and has potential health hazards to human body. Objective Based on network toxicology and molecular docking technology, the compounds that may cause hepatotoxicity in triclosan were predicted and the mechanism was discussed. Method From April to May 2025, the targets of triclosan were identified using databases such as STITCH, CTD, Swiss Target Prediction, and TargetNet. Additionally, gene targets associated with liver toxicity were identified from the GeneCards and OMIM databases. The intersection of triclosan-targets and liver toxicity-related gene targets was used to identify candidate targets. Using the String platform, a protein interaction network was constructed for these candidate targets to identify core functional modules within the network. The candidate targets were analyzed for GO and KEGG enrichment using DAVID, and a triclosan-liver toxicity-target pathway network was constructed using Cytoscape 3.10.1 software. Network topology analysis was conducted to screen for key components and targets. Finally, molecular docking was performed on the core targets using CB-Dock2. Results 683 candidate targets for liver toxicity caused by triclosan were identified. The core targets for liver toxicity from triclosan production include TP53, EGFR, AKT1, IL6, JUN, and FN1 . Molecular docking analysis shows that the binding free energy of triclosan with these core targets is less than −5.5 kcal/mol. The comprehensive analysis results showed that the liver damage caused by triclosan was mainly related to the activation of Pathways in cancer, Endocrine resistance, AGE-RAGE signaling pathway in diabetic complications, hepatitis B, and lipid and atherosclerosis signaling pathways. Conclusion The potential targets and molecular mechanisms of triclosan (TCS) induced liver injury were investigated, and 6 key targets and 5 pathways were identified, providing a new paradigm for evaluating the health risks caused by environmental pollutants.